Impacts of spatial variability in urban hydrological modelling: a case study of the Canal do Mangue Basin in Rio de Janeiro, Brazil - James de Melo Sampaio Júnior; Marcelo de Miranda Reis; Igor da Silva Rocha Paz (Revista Brasileira de Recursos Hídricos, 2025)
ABSTRACT This study analyzes spatial and rainfall variability of an urban basin using the Stormwater Management Model (SWMM), a semi-distributed and open-source hydrological tool. The Canal do Mangue Basin (CMB) in the city of Rio de Janeiro, Brazil, was modelled with three map resolutions, varying the numbers of sub-basins, and three rainfall spatialization methods: arithmetic mean, Thiessen polygons, and Inverse Distance Weighted (IDW). Simulated water levels were compared to observed data at control points, considering different rain gauge densities. Results showed good agreement between observed and simulated volumes. The arithmetic mean method performed best overall, with errors ranging from 0.00% to 18.60%, while IDW showed higher accuracy for specific nodes (10.82% to 15.18%). The study concludes that spatial resolution, interpolation methods, and rain gauge density significantly affect model performance, providing valuable insights for optimizing hydrological modeling in urban basins.